MICROCONTROLLER BASE SPIN COATING DESIGN AND IoT DATA MONITORING AND STORAGE - Sya'roni, Imam; Hartanto, Anton; Rahman, Nizar Rizki; Subiantoro, Irfan (Indonesian Physical Review, 2023)
This research is the development of a research support tool, namely Spin Coating. In addition to the high price factor and limited maintenance on the equipment that has been purchased, the researcher wants to design a spin coating tool to support laboratory equipment. Not only to get a relatively affordable price but also to be able to develop homemade tools that have precise measurement capabilities, and good quality results because they use a microcontroller in the tool's work settings. Therefore, researchers created a new design for a spin coating tool with IoT technology to make it easier for laboratory users to monitor it from anywhere and anytime and storage real time. The research method is Research and Development with the stages of design calibration, and testing of tools. From the results of making the tool, the resolution of the tool through the linearity of the sensor used is 99.71% with the power value of each RPM, namely 178.05 RPM/W. The IoT innovation on the spin coating tool runs smoothly using cloud.